2006
DOI: 10.1071/ar05340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xylanase supplementation on between-bird variation in energy metabolism and the number of Clostridium perfringens in broilers fed a wheat-based diet

Abstract: Three experiments were conducted to examine: (a) the apparent metabolisable energy (AME) contents, the level of non-starch polysaccharides (NSP), and the extract viscosity value of 9 wheat samples; (b) the efficacy of a xylanase in reducing between-bird variation for AME; and (c) the effect of a xylanase on the number of Clostridium perfringens in broilers fed a low AME wheat diet. Experiment 1 revealed that the AME value of wheat varied from 11.5 to 13.6 MJ/kg dry matter (DM), which negatively correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Regarding the effects of xylanase supplementation on NE incidence, few reports in the literature are found. Choct et al (2006) demonstrated that xylanase supplementation reduced C. perfringens numbers in the caeca of healthy broiler chickens fed wheat-based diets. Jia et al (2009) showed that enzyme supplementation did not affect the growth of C. perfringens, but it ameliorated the retarded growth by disease challenge through improving the feed conversion ratio in birds consuming the wheatbased diets.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effects of xylanase supplementation on NE incidence, few reports in the literature are found. Choct et al (2006) demonstrated that xylanase supplementation reduced C. perfringens numbers in the caeca of healthy broiler chickens fed wheat-based diets. Jia et al (2009) showed that enzyme supplementation did not affect the growth of C. perfringens, but it ameliorated the retarded growth by disease challenge through improving the feed conversion ratio in birds consuming the wheatbased diets.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous reports. (Yin et al, 2000;Choct et al, 2006;Mirzaie et al, 2012). Digest NSP of wheat and barley by carbohydrases has been successful and promising in broilers (Olukosi et al, 2007;Slominski, 2011).…”
Section: Effect Of Non-starch Polysaccharide (Nsp) Of Wheat and Barlementioning
confidence: 99%
“…Sedentary intestinal digesta and low oxygen condition due to indigestible NSP provide an appropriate environment for fermentative anaerobic bacteria proliferation (Langhout et al, 1999). The decrease in nutrient availability and production of detrimental by-products resulted in microbial changes throughout the gut (Choct et al, 2006). Water soluble fraction of barley NSP has a deleterious effect on intestinal physicochemical characteristics and microbial proliferation of chickens (Choct, 1997;.…”
Section: Effect Of Non-starch Polysaccharide (Nsp) Of Wheat and Barlementioning
confidence: 99%
“…According to the results of one research, slow movement of digesta and low oxygen condition due to the presence of NSP provide a stable media, where fermentative microbes such as anaerobic bacteria proliferate easily [12]. Such microbial changes reduce nutrients available for host and produce detrimental by-products [4]. Water soluble NSPs of wheat were reported to have deleterious impact on physicochemical properties and microbial proliferation of digesta in the intestinal tract of chickens [3,4].…”
Section: Discussionmentioning
confidence: 99%